Предмет: Математика,
автор: xckorrrpionxQT
2/(дробь)3-х + 1/2 = 6/х(3-х)
Ответы
Автор ответа:
0
2/(3-х) + 1/2 - 6/(х(3-х)) = 0
(2*2х + х(3-х) - 6*2) / 2х(3-х) = 0
4х + 3х - х^2 - 12 = 0, при этом 2х(3-х) ≠ 0
x^2 - 7x + 12 = 0 x ≠ 0, 3-x ≠ 0
d = 49 - 48 = 1 x ≠ 3
x1 = (7-1)/2 x2 = (7+1)/2
x1 = 3 x2 = 4
х1 - посторонний корень, так как по ОДЗ х ≠ 3
Ответ: x2 = 4
(2*2х + х(3-х) - 6*2) / 2х(3-х) = 0
4х + 3х - х^2 - 12 = 0, при этом 2х(3-х) ≠ 0
x^2 - 7x + 12 = 0 x ≠ 0, 3-x ≠ 0
d = 49 - 48 = 1 x ≠ 3
x1 = (7-1)/2 x2 = (7+1)/2
x1 = 3 x2 = 4
х1 - посторонний корень, так как по ОДЗ х ≠ 3
Ответ: x2 = 4
Похожие вопросы
Предмет: Математика,
автор: m6855030
Предмет: Биология,
автор: mamenovroman20041
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: derbo1979
Предмет: Литература,
автор: Jesica2013